Public relations, professionalism, and the public interest - Bivins, Thomas H. (Journal of business ethics, 1993)
The public interest statement contained in the PRSA Code of Professional Standards is unduly vague and provides neither a working definition of “public interest” nor any guidance for the performance of what most professions consider to be a primary value. This paper addresses the question of what might constitute public relations service in the public interest, and calls for more stringent guidelines to be developed whereby the profession may advance its service goals more clearly.